2009
DOI: 10.1002/yd.312
|View full text |Cite
|
Sign up to set email alerts
|

From voice to agency: Guiding principles for participatory action research with youth

Abstract: This article begins by examining current crises facing historically marginalized youth, which necessitate more critical approaches to youth development and empirical investigations into the challenges that young people face. This requires not only listening to their voices, but actively engaging them in investigations of and interventions into social problems that affect their lives. Researching with youth raises particular dilemmas, however. The authors discuss strategies, within three guiding principles, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(216 citation statements)
references
References 8 publications
1
200
0
2
Order By: Relevance
“…The thread that weaves through such accounts, whether explicitly or implicitly, is the extent to which empowerment of the 'users' takes place in relation to decision-making, contributions, confidence and relationships. Rodríguez and Brown (2009) characterise this as participants moving from 'voice' to 'agency', with a concomitant shift from the 'expert' position of university researchers to a more shared notion of power and decision-making in research.…”
Section: Conceptualisations Of Designing Technology With and For Chilmentioning
confidence: 99%
“…The thread that weaves through such accounts, whether explicitly or implicitly, is the extent to which empowerment of the 'users' takes place in relation to decision-making, contributions, confidence and relationships. Rodríguez and Brown (2009) characterise this as participants moving from 'voice' to 'agency', with a concomitant shift from the 'expert' position of university researchers to a more shared notion of power and decision-making in research.…”
Section: Conceptualisations Of Designing Technology With and For Chilmentioning
confidence: 99%
“…We later returned to two of the schools to run participatory action research (PAR) clubs (see, among many, Cammarota & Fine, 2008;Rodríguez & Brown, 2009) with students over several weeks in August 2015 (Metsi School) and February 2016 (Ami School). 3 In these clubs, we first presented preliminary findings from the initial phase of research and then worked with students to explore those findings they found most relevant and interesting through additional data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Participatory action research is guided by a critical paradigm, which allows marginalised voices to become centre stage (Rodríguez & Brown, 2009) and so performs an educative and transformative role (Babbie & Mouton, 2010). A critical paradigm enabled us to work with them to raise their awareness of teenage pregnancy and enable them to devise strategies to deal with the issues it raises to improve the situation as it affects their lives (Mertens, 2009).…”
Section: Theoretical Framingmentioning
confidence: 99%